Cardiofaciocutaneus syndrome: literature review and case report - V. V. Umnov; N. V. Nikitina; A. M. Khodorovskaya; O. V. Barlova (Нервно-мышечные болезни)
The cardiofaciocutaneous syndrome is a condition of sporadic occurrence, with patients showing multiple congenital anomalies and mental retardation. The syndrome is caused by molecular disturbances in the RAS/MAPK pathway. We report on the girl, 9 year-old, with the cardiofaciocutaneous syndrome presenting with typical craniofacial appearance, heart defects, ectodermal abnormalities, neglected orthopedic pathology, developmental delay and spasticity, which rare in this syndrome.